Right: Fanya Baron: In Dubinsky’s letter to Fleshin and Steimer of 10.11.1931 we find: “I’m attaching a photograph of Fanya Baron. She’s marked by an “X” and holding a child belonging to her sister, who is standing above her. This photograph was given to me by Semka." (IISH, Senya Fléchine Papers, Folder 87)
Right: Fanya Baron: In Dubinsky’s letter to Fleshin and Steimer of 10.11.1931 we find: “I’m attaching a photograph of Fanya Baron. She’s marked by an “X” and holding a child belonging to her sister, who is standing above her. This photograph was given to me by Semka." (IISH, Senya Fléchine Papers, Folder 87).